2021
DOI: 10.3390/pathogens10080921
|View full text |Cite
|
Sign up to set email alerts
|

Subtractive Genomics Approach for Identification of Novel Therapeutic Drug Targets in Mycoplasma genitalium

Abstract: Mycoplasma genitalium infection is a sexually transmitted infection that causes urethritis, cervicitis, and pelvic inflammatory disease (PID) in men and women. The global rise in antimicrobial resistance against recommended antibiotics for the treatment of M. genitalium infection has triggered the need to explore novel drug targets against this pathogen. The application of a bioinformatics approach through subtractive genomics has proven highly instrumental in predicting novel therapeutic targets against a pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 76 publications
(80 reference statements)
0
16
0
Order By: Relevance
“…Two proteins, i.e., chromosomal replication initiator protein DnaA and two-component response regulator (TCR), were found to be involved in unique metabolic pathway, i.e., a two-component system, and identified as novel drug targets. Several other studies have also reported DnaA [56,57] as a drug target.…”
Section: Discussionmentioning
confidence: 90%
“…Two proteins, i.e., chromosomal replication initiator protein DnaA and two-component response regulator (TCR), were found to be involved in unique metabolic pathway, i.e., a two-component system, and identified as novel drug targets. Several other studies have also reported DnaA [56,57] as a drug target.…”
Section: Discussionmentioning
confidence: 90%
“…The complete proteome of Moraxella catarrhalis BBH18 was eradicated at 60% threshold using Cluster Database at High Identity with Tolerance i.e. CD-HIT [ 20 , 21 ].The proteins possessing the sequence identity greater than 60% are paralogous to each other. The complete sequences of paralogous i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Further, the set of proteins retrieved after removal of paralogous were subjected to BLASTp [ 22 ] with the expectation value (i.e. E-value) cut-off of 10 −5 against Homo sapiens proteome [ 21 ]. The BLASTp generated results i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some receptive membranes are also classified as “anti-target.” They are adrenergic α1a, dopaminergic D2, muscarinic M1, and serotonergic 5-HT2C. A total of 210 human “anti-targets” have been identified in the literature ( 106 ), and the corresponding sequences of these proteins have been obtained from the NCBI protein database. BLASTp analysis was carried out for all nonhomologous, essential “novel drug target” proteins against these “anti-targets,” setting an E value threshold of <0.005, a query length of >30%, and an identity of <30% as parameters.…”
Section: Methodsmentioning
confidence: 99%